INTELLECTUAL CAPITAL IMPACT PADA FINANCIAL PERFORMANCE PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yateno Yateno (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2019)
The purpose of this research was to examine the effect of intellectual capital on Return On Assets, and Return On Equity. The population of this research is manufacturing companies listed on the Stock Exchange the period 2016- 2018, a total sample of companies amounted to 72 samples were taken by using purposive sampling method. The method of analysis in this research is multiple linear regression analysis. The results of this study indicate that intellectual capital significant positive effect on ROA. This condition occurs because when intellectual capital is getting better, the public trust in the company, the better, so that the products or services offered by the company is accepted by the community and increasing revenue. Intellectual capital is significant positive effect on ROE. This condition occurs because the intellectual capital increases, the company has been using its capital more effectively to improve human resources, so that the performance of employees to generate increasing profits. Keyword: Intellectual Capital, Financial Performance, Return on Assets and Return On Equity